2018
DOI: 10.1177/1528083718804208
|View full text |Cite
|
Sign up to set email alerts
|

All-fabric flexible supercapacitor for energy storage

Abstract: An all-fabric solid-state flexible supercapacitor has been fabricated using three types of commercial woven fabrics made of carbon fiber, activated carbon fiber, and polyester fiber, respectively. The activated carbon fiber fabric is viscose-based twill through carbonization and activation, followed by a deposition of CeO2 or ZnO nanoparticles through a hydrothermal process. The resultant fabric supercapacitor displays a high specific capacitance of 13.24 mF cm−2 at a scan rate of 0.2 mV s−1, an excellent capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Lee et al [303] developed an asymmetric SC by assembling MnO 2 @CPPy and carbon coated Co 3 O 4 microsheet (Co 3 O 4 @C)-decorated carbon cloths with a solid-state PVA/KOH electrolyte, which retained 97% capacitance after 500 bending cycles. Luo et al [396] reported an increase of 13.4% capacitance after 200 bending cycles for an all-fabric solid-state flexible SC, made of activated carbon fiber fabric, Figure 18(e,f). The capacitance of a solid-state stretchable SC, prepared by assembling VPPyNTs/CNOs@PPyG-textile electrodes with a PVA/H 3 PO 4 gel electrolyte into a sandwiched structure, was nearly unchanged after stretching for 500 cycles at a strain of 50%.…”
Section: Flexibilitymentioning
confidence: 98%
See 3 more Smart Citations
“…Lee et al [303] developed an asymmetric SC by assembling MnO 2 @CPPy and carbon coated Co 3 O 4 microsheet (Co 3 O 4 @C)-decorated carbon cloths with a solid-state PVA/KOH electrolyte, which retained 97% capacitance after 500 bending cycles. Luo et al [396] reported an increase of 13.4% capacitance after 200 bending cycles for an all-fabric solid-state flexible SC, made of activated carbon fiber fabric, Figure 18(e,f). The capacitance of a solid-state stretchable SC, prepared by assembling VPPyNTs/CNOs@PPyG-textile electrodes with a PVA/H 3 PO 4 gel electrolyte into a sandwiched structure, was nearly unchanged after stretching for 500 cycles at a strain of 50%.…”
Section: Flexibilitymentioning
confidence: 98%
“…Reproduced with permission. [396] Copyright 2020, SAGE Publications. bending of SC devices for hundred to several hundred cycles is performed at various angles to evaluate the flexibility of a SC device.…”
Section: Flexibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Textiles with thermoelectrical properties are of interest in a wide range of commercial and industrial applications like personal thermoregulation, 4 energy harvesting, [5][6][7] or antiice/de-ice systems. 8,9 Their heating behavior is explained through Joule's effect, which states that the electric current circulating in a conductive material causes power loss in the form of heat generation 10 and this behavior can easily be used to warm up fabrics if they have the proper level of conductivity.…”
Section: Introductionmentioning
confidence: 99%